Application of Set Pair Analysis Method Based on Entropy Weight in Groundwater Quality Assessment -A Case Study in Dongsheng City, Northwest China. Issue 2 (2011) - Pei-Yue, Li; Hui, Qian; Jian-Hua, Wu
Abstract : Groundwater quality assessment is an essential study which plays important roles in the rational development and utilization of groundwater. Groundwater quality greatly influences the health of local people. However, most traditional water quality comprehensive assessment methods which have complicated formulas are difficult to apply in water quality assessment. In this paper, a novel method for groundwater quality assessment called set pair analysis was introduced and entropy weight was assigned to each index to improve the assessment model. The calculation steps are depicted in the paper and take groundwater quality assessment in Dongsheng City as a case study. The assessment results indicated that groundwater qualities in the study area were relatively good, Set Pair Analysis method, which was an optimal method for groundwater quality assessment and worth promoting, was easy to use and calculation processes which use almost all the relative information were simple, results were reasonable, reliable and intuitive.